Komitmen Perseroan Terbatas Terhadap Pencantuman Klausula Tanggung Jawab Sosial Dan Lingkungan Dalam Akta Pendirian Perseroan Terbatas Di Kota Bengkulu - Elsa Romana Widyarni; Edra Satmaidi; Widiya N. Rosari (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
This study aims to analyze the commitment of Limited Liability Company (PT) founders in Bengkulu City regarding the inclusion of Social and Environmental Responsibility (TJSL/CSR) clauses in the Deed of Establishment, and to analyze the legal implications for companies that fail to fulfill this obligation. The background of this research is based on the phenomenon of numerous companies in Bengkulu with